(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Primary fallopian tube carcinoma (PFTC) is one of the rarest malignancies of female genital tract. It represents <1% of all gynecologic malignancies. Preoperative diagnosis is uncommon due to its rarity and non-specific symptoms. In most cases diagnosis is made during surgery or histological examination. Rarity of this type of carcinoma prompted us to report it as individual case. Case: A 40-yearold parous women presented with bilateral PFTC. The patient gave a history of lower abdominal and pelvic pain for 2 years on several occasions. An abdominal ultrasound finding showed an adnexal mass and her CA125 level was 30IU/ml (normal- <35IU/ml). Clinically she was suspected as a case of pelvic inflammatory disease (PID). She underwent Total Abdominal Hysterectomy with bilateral salpingoophorectomy. Intraoperative findings were consistent with PID. Final pathologic analysis showed bilateral primary fallopian tube carcinoma —well differentiated serous adenocarcinoma. Post operatively she was referred for oncological management. Conclusion: Malignancy should be considered in the differential diagnosis of PID especially in premenopausal age and intraoperative frozen section biopsy is crucial to make correct diagnosis and to allow appropriate surgical staging. J Bangladesh Coll Phys Surg 2020; 38(1): 49-52